Polychlorinated biphenyls and chlorinated paraffins in home-produced eggs from an e-waste polluted area in South China: Occurrence and human dietary exposure. (July 2018) - Zeng, Yanhong; Huang, Chenchen; Luo, Xiaojun; Liu, Yine; Ren, Zihe; Mai, Bixian
Abstract: The levels of polychlorinated biphenyls (PCBs) and short/median-chain chlorinated paraffins (S/MCCPs) in 68 home-produced eggs collected in 2013 and 2016 from an electronic-waste (e-waste) site in South China were measured and the human dietary exposure to these two classes of contaminants via egg consumption was calculated. The levels of PCBs, SCCPs, and MCCPs varied from 236 to 8870 ng/g lipid weight (lw), 477 to 111, 000 ng/g lw, and 125 to 91, 100 ng/g lw, respectively. There are no significant differences in the levels of PCBs, SCCPs, and MCCPs between 2013 and 2016 ( p  > 0.05). The congener profiles of PCBs and MCCPs were similar to each other between 2013 and 2016; however, the homologue profiles of SCCPs were different. The Toxic Equivalent Quantities (TEQs) of ∑DL-PCBs and the levels of ∑ICES-6 PCBs strongly exceeded the limits set by EU Regulation 1259/2011 (2.5 pg World Health Organization-TEQ2005 g −1 lw for DL-∑PCBs and 40 ng/ g lw for ∑ICES-6 PCBs). The estimated daily intakes (EDI) of PCBs, SCCPs, and MCCPs by adults and children ranged between 5.57 and 1100, 11.8 and 11, 900, and 3.62 and 11, 400 ng/kg bw/d, respectively. PCBs pose serious health risks for local residents, especially for children, due to the high ratios of EDI (68% in 2013 and 70% in 2016 for adults and 100% for children) in excess of the exposure limits. Highlights: High levels of PCBs and S/MCCPs are frequently detected in free-range eggs. Different homologue profiles of SCCPs were found between the two sampling times. Toxic Equivalent Quantities of PCBs strongly exceeded the limit set by EU Regulation. Consuming these home-produced eggs implicates a serious risk for local residents.